1977
DOI: 10.1289/ehp.772125
|View full text |Cite
|
Sign up to set email alerts
|

Inhalation toxicity of vinyl chloride and Vinylidene chloride

Abstract: Exposure of mice to 1000 ppm of vinyl chloride (VC), 6 hr/day, 5 days/week, caused some acute deaths with toxic hepatitis and marked tubular necrosis of the renal cortex. Starting the sixth month, mice exposed to 1000, 250, or 50 ppm of VC became lethargic, lost weight quickly, and died. Only a few mice exposed to 50 ppm survived for 12 months. Pulmonary macrophage count was elevated in some mice. There was a high incidence of bronchiolo-alveolar adenoma, mammary gland tumors including ductular adenocarcinoma,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

1977
1977
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…While in keeping with the observations made by other authors [4,7], the present results pro vide limited evidence of carcinogenicity of VDC in rodents. Additional evidence on which to base a final assessment of the carcinogenicity of VDC may be forth coming from studies known to be underway [15].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…While in keeping with the observations made by other authors [4,7], the present results pro vide limited evidence of carcinogenicity of VDC in rodents. Additional evidence on which to base a final assessment of the carcinogenicity of VDC may be forth coming from studies known to be underway [15].…”
Section: Discussionsupporting
confidence: 88%
“…The results of a number of long term carcinogenicity tests have recently become avail able, either as preliminary communications or as interim results of on-going studies [4][5][6], The preliminary re sults of one study, in which VDC was given by inhala tion, point to the induction of kidney carcinoma in mice and to an increased incidence of mammary tumours in rats, no carcinogenic effect was observed when VDC was administered by the oral route to rats or hamsters [4], An increased incidence of lung, skin and liver cell tumours in mice and the induction of haemangiosarcomas in both mice and rats was reported in another inhalation study [7], In addition, VDC has been shown to be mutagenic to Salmonella typhimurium [8], Chloroprene (CP) is used as a chemical intermediate, mainly as the monomer in the manufacture of synthetic elastomers. World production of this compound in 1977 is estimated to have been 300,000 t.…”
Section: Introductionmentioning
confidence: 98%
“…Survivors of AKI have up to a 28-fold are at higher risk for CKD than healthy individuals [29,30]. Previous studies showed that VC resulted in acute death with marked tubular necrosis of the renal cortex when mice were exposed to high doses of VC [31]. Other studies have shown that autophagy may attenuate fibrosis [32].…”
Section: Introductionmentioning
confidence: 99%
“…The ultrastructure was thought to indicate that the tumors originated in type II alveolar cells. Alveologenic tumors were also described in several other experimental studies (25)(26)(27). Interestingly, other known carcinogens, such as polycyclic aromatic hydrocarbons, nitrogen mustard and chromates, produce pulmonary tumors in experimental animals similarly, originating in the type II alveolar cell.…”
mentioning
confidence: 64%